Surface hydrophobically modified gypsum-aerogel composite thermal insulation material as well as preparation method and application thereof
通过将亲水气凝胶与石膏共混合,并进行硅烷偶联剂的表面疏水改性,解决了石膏基复合材料在潮湿环境下性能降低的问题,实现了高保温性能和美观度的石膏-气凝胶复合材料。
Patent Information
- Application Number
- CN202411700985.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-25
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2044-11-25
AI Technical Summary
Existing gypsum-based composite materials are prone to decrease mechanical strength and insulation properties in humid environments, and the hydrophobic aerogels are poorly compatible with gypsum, making them difficult to mix, resulting in poor product aesthetics.
By co-mixing hydrophilic aerogel with low thermal conductivity with gypsum and surface hydrophobic modification is performed using silane coupling agent to form a surface hydrophobic gypsum-aerogel composite.
It significantly improves the thermal insulation performance of gypsum materials, and the thermal conductivity can be as low as 0.08W/(m·K), while maintaining the mechanical strength and aesthetics of the material, which is suitable for humid environments.
Smart Images

Figure CN119462053A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of solid waste resource utilization, and specifically relates to a surface hydrophobically modified gypsum-aerogel composite thermal insulation material and a preparation method and application thereof. Background Art
[0002] With the continuous development of my country's industry, the output of industrial by-product gypsum has increased year by year. The current annual emission is about 220 million tons, and the accumulated stockpile exceeds 1 billion tons, causing serious land occupation problems and potential environmental pollution risks. Using industrial by-product gypsum as raw material to prepare gypsum-based building materials is a relatively mature way of resource utilization. Compared with cementitious materials such as cement and lime, it has low production energy consumption, low carbon emissions and certain thermal insulation properties. The thermal conductivity is about 0.3-0.5W / (m·K), but it is still difficult to meet the performance requirements of building insulation materials. The thermal insulation performance of gypsum-based materials can be enhanced by combining gypsum as the main material with lightweight aggregates. The obtained lightweight insulation materials have been recognized and applied in the construction field. Compared with traditional lightweight aggregates, aerogels have good thermal insulation performance and a thermal conductivity as low as 0.02W / (m·K). They can better improve the thermal insulation performance of gypsum products, make them meet the standards of thermal insulation building materials, and realize the resource utilization of industrial by-product gypsum.
[0003] A Chinese invention patent (publication number CN1 13461404A) discloses a SiO2 aerogel-gypsum-based thermal insulation material and its preparation method. This method does not use other additives, directly mixes hydrophobic SiO2 aerogel into gypsum for co-hydration, and obtains SiO2 aerogel-gypsum-based thermal insulation material with good thermal insulation performance after drying. However, the aerogel is easy to float and aggregate during the mixing process, and has poor compatibility with gypsum. The obtained product contains a large number of honeycomb holes, has poor aesthetics, and is not suitable for direct use.
[0004] A Chinese invention patent (publication number CN1 13429184A) discloses a paper-faced gypsum board and its preparation method. The method mixes aerogel and clay to form granules, and then mixes the obtained aerogel particles into gypsum building materials to solve the problem of poor compatibility between aerogel and gypsum matrix. The obtained aerogel gypsum board has a dense structure and good thermal insulation performance. However, it is difficult to granulate aerogel powder, and multiple adhesives and foaming agents need to be added, which makes the process complicated.
[0005] A Chinese invention patent (publication number CN1 16143486A) discloses a thermal insulation gypsum and a preparation method thereof. With the assistance of a retarder and an air entraining agent, the method achieves uniform dispersion of aerogel in the gypsum by combining vacuum stirring and normal pressure stirring, thereby enhancing the thermal insulation performance of the material. However, the hydrophobicity of the material is still not improved, and the mechanical strength and thermal insulation performance are easily reduced after water absorption, and the application scope in humid environments is still relatively limited.
[0006] In summary, in actual applications, hydrophobic aerogels are usually selected as raw materials to ensure that gypsum-based composite materials can maintain high thermal insulation performance in humid environments. However, hydrophobic aerogels are prone to floating during mixing with gypsum, difficult to mix with gypsum during co-hydration, and poor compatibility. Moreover, after the addition of hydrophobic aerogels, the overall hydrophilicity of the composite material cannot be changed. After absorbing water, the mechanical strength and thermal insulation performance are easily reduced, and the scope of application in humid environments is still relatively limited. Summary of the invention
[0007] In view of the defects of the prior art, the present invention provides a surface hydrophobic-modified gypsum-aerogel composite thermal insulation material and a preparation method and application thereof, the purpose of which is to circumvent the technical problems in the prior art that the hydrophobic aerogel has poor compatibility with gypsum and the mechanical strength and thermal insulation performance of the product are reduced after water absorption, and obtain a gypsum-aerogel composite thermal insulation material with good thermal insulation performance, a smooth surface and hydrophobicity.
[0008] According to a first aspect of the present invention, a method for preparing a surface hydrophobically modified gypsum-aerogel composite thermal insulation material is provided, characterized in that it comprises the following steps:
[0009] (1) mixing CaSO4·0.5H2O gypsum powder with a purity of 85% to 95% and hydrophilic aerogel powder with a thermal conductivity of 0.01 to 0.02 W / (m·K) in a mass ratio of 3 to 6, then adding water, injection molding and curing, and then drying at 40 to 60° C. to obtain a hydrophilic gypsum-aerogel composite material;
[0010] (2) The hydrophilic gypsum-aerogel composite material is immersed in a silane coupling agent solution for modification, and then dried to obtain a gypsum-aerogel composite material with a hydrophobic surface.
[0011] Preferably, the CaSO4·0.5H2O gypsum powder is obtained by calcining and aging gypsum containing CaSO4·2H2O, the calcination temperature is 140-180°C, the calcination time is 1-4h, and the aging time is 1-3 days.
[0012] Preferably, the CaSO4·2H2O-containing gypsum is one or more of desulfurized gypsum, phosphogypsum, fluorinated gypsum, and citric acid gypsum.
[0013] Preferably, the hydrophilic aerogel powder material is selected from one or more of silica aerogel, alumina aerogel, and carbon aerogel, and the pore size of the hydrophilic aerogel powder is 20 to 40 nm.
[0014] Preferably, in step (1), the ratio of the added volume of the water to the sum of the weights of the CaSO4·0.5H2O gypsum powder and the hydrophilic aerogel powder is 1.2-1.8 mL / g.
[0015] Preferably, in step (1), the injection molding curing conditions are: curing temperature is 15-25° C., relative humidity is 80%-90%, and curing time is 1-3 days.
[0016] Preferably, in step (2), the silane coupling agent solution is prepared by adding a silane coupling agent to a solvent, the silane coupling agent is selected from one or more of trimethylchlorosilane, octadecyltrichlorosilane, and methyltrimethoxysilane, and the volume ratio of the solvent to the silane coupling agent is 80 to 100.
[0017] Preferably, in step (2), the mass volume ratio of the hydrophilic gypsum-aerogel composite material to the silane coupling agent solution is 1.0 to 1.5 g / mL, and the immersion time is 3 to 5 hours.
[0018] According to another aspect of the present invention, a method for preparing the surface hydrophobic-modified gypsum-aerogel composite thermal insulation material is provided to prepare the surface hydrophobic gypsum-aerogel composite material.
[0019] According to another aspect of the present invention, there is provided an application of the surface-hydrophobic gypsum-aerogel composite material, wherein the surface-hydrophobic gypsum-aerogel composite material is used as a thermal insulation material in a building.
[0020] The principle of the method of the present invention is as follows: firstly, industrial by-product gypsum rich in CaSO4·2H2O is calcined, aged and then dehydrated to obtain industrial by-product building gypsum powder rich in CaSO4·0.5H2O, industrial by-product building gypsum powder rich in CaSO4·0.5H2O is mixed with hydrophilic aerogel powder and then water is added, the hydrophilic aerogel powder is physically doped with the industrial by-product building gypsum powder rich in CaSO4·0.5H2O, the hydrophilic aerogel powder does not participate in the hydration of gypsum, and still exists in a nano-network structure, after the industrial by-product building gypsum powder rich in CaSO4·0.5H2O is added with water, after complete hydration, CaSO4·0.5H2O is completely converted into CaSO4·2H2O, and the hydrophilic gypsum-aerogel composite material is obtained at this time, and the obtained hydrophilic gypsum-aerogel composite thermal insulation material is impregnated and modified using a silane coupling agent solution. The crystal water carried by the gypsum can interact with water molecules or other polar molecules in the air through hydrogen bonds to form hydroxyl groups. The Si-C1 bond in the silane coupling agent molecule can be hydrolyzed to generate a Si-OH group, which can dehydrate with the hydroxyl group on the gypsum surface to form a stable Si-O-Si bond, thereby grafting the hydrophobic alkyl network on the silane coupling agent onto the gypsum surface to obtain a surface hydrophobic gypsum-aerogel composite material.
[0021] In general, the above technical solution conceived by the present invention has the following technical advantages compared with the prior art:
[0022] (1) The present invention mixes a hydrophilic aerogel having a thermal conductivity of 0.01 to 0.02 W / (m·K) with an industrial by-product building gypsum rich in CaSO4·0.5H2O, and improves the thermal insulation performance of the gypsum substrate by externally doping the hydrophilic aerogel with low thermal conductivity; since the hydrophilic aerogel is combined with the industrial by-product gypsum in the form of physical doping, the hydrophilic aerogel does not participate in the hydration of the gypsum, and thus the hydrophilic aerogel still exists in a nano-network structure, which increases the heat transfer path, so that the material as a whole has a larger thermal resistance, and can significantly The thermal insulation performance of gypsum materials is significantly improved; the pore size distribution of hydrophilic aerogel is selected to be 20-40nm, because the pore size is smaller than the mean free path of air under standard conditions (69nm). This nanoscale pore will severely restrict the free movement of molecules, thereby greatly reducing the thermal conductivity of the gas and improving the thermal insulation performance of the material; in addition, at the same time, due to the good compatibility of hydrophilic aerogel with gypsum, the aerogel and gypsum can be evenly mixed without the addition of external chemical reagents, solving the problem of difficult mixing and poor compatibility of hydrophobic aerogel and gypsum.
[0023] (2) The present invention achieves hydrophobic modification of the surface of the hydrophilic gypsum-aerogel composite material by immersion treatment with an external hydrophobic modifier silane coupling agent, thereby achieving overall hydrophobicity of the composite material. At the same time, the modification process does not involve the destruction of the internal structure of the material, so it has no significant effect on the mechanical strength and thermal insulation performance of the composite material.
[0024] (3) The purpose of preparing industrial by-product building gypsum powder with CaSO4·0.5H2O is to obtain a material with high mechanical strength. CaSO4·0.5H2O has a fast hydration rate and the generated crystals are intertwined and are the main source of the strength of industrial by-product gypsum. When the content of dihydrate gypsum is high, the strength of desulfurized building gypsum will be significantly reduced. When the content of anhydrous gypsum is too high, the initial setting of desulfurized building gypsum will be too short, and the calcined gypsum cannot be processed and used. Since aerogel does not have structural strength, the mechanical strength of the composite material after being mixed with gypsum is correspondingly reduced. Therefore, the use of CaSO4·0.5H2O is crucial to the strength of the composite material after molding.
[0025] (4) The present invention selects industrial by-product gypsum rich in CaSO4·2H2O as the raw material of the surface hydrophobically modified gypsum-aerogel composite thermal insulation material, thereby utilizing the industrial by-product gypsum as a resource and avoiding resource waste. At the same time, the prepared thermal insulation material can be used in the field of building thermal insulation, providing a new choice for my country's building energy-saving materials.
[0026] (5) The surface hydrophobic gypsum-aerogel composite material obtained by the present invention has a thermal conductivity as low as 0.08W / (m·K), and the compressive and flexural strengths can still be maintained at more than 1.8MPa and 0.7MPa, respectively, meeting the Type II standard specified in "Building Thermal Insulation Mortar" GB / T20473-2021. At the same time, the static water contact angle can reach 120°, and the softening coefficient can reach more than 0.8, which is sufficient to resist a humid environment, and the surface of the finished product with a hydrophobic surface of the gypsum-aerogel composite material is smooth, without irregular pores, and has good aesthetics. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 It is a process flow chart of the present invention;
[0028] Figure 2 The schematic diagram of the surface hydrophobic modification of hydrophilic gypsum-aerogel composite material is shown in Figure 1, taking trimethylchlorosilane and octadecyltrichlorosilane as examples;
[0029] Figure 3 (a) morphology and (b) static water contact angle of the hydrophobic gypsum-aerogel composite prepared in Example 1;
[0030] Figure 4(a) morphology and (b) surface static water contact angle of the gypsum-aerogel composite material prepared in Comparative Example 3.
[0031] Figure 5 XRD pattern of gypsum-aerogel composite insulation material with surface hydrophobic modification DETAILED DESCRIPTION
[0032] In order to make the purpose, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. In addition, the technical features involved in the various embodiments of the present invention described below can be combined with each other as long as they do not conflict with each other.
[0033] Embodiment 1:
[0034] Preparation of surface hydrophobically modified gypsum-aerogel composite insulation material:
[0035] (1) Desulfurized gypsum (from Zhejiang Lanxi Power Plant, the same below) was calcined in an oven at 160° C. for 3 h and then aged for 2 days in an environment at 20° C. and a relative humidity of 80% to obtain desulfurized building gypsum powder;
[0036] (2) After dry mixing and stirring the desulfurized building gypsum powder and silica hydrophilic aerogel powder (thermal conductivity of 0.018 W / (m·K)), the water-powder ratio (V 水 :m (脱硫建筑石膏粉+亲水气凝胶粉末) ) is 1.8 mL / g, water is added and stirred to obtain a gypsum-aerogel mixed slurry;
[0037] (3) injecting the gypsum-aerogel mixed slurry into a mold, curing it in an environment of 20° C. and a relative humidity of 80% for 3 days, and then drying it to obtain a hydrophilic gypsum-aerogel composite material;
[0038] (4) Octadecyltrichlorosilane was dissolved in n-hexane to obtain an octadecyltrichlorosilane solution, and the hydrophilic gypsum-aerogel composite material was immersed in the octadecyltrichlorosilane solution at a mass volume ratio of 1.0 g / mL for 5 h, and the volume ratio of the solvent n-hexane to octadecyltrichlorosilane was 80 v / v. After the modification was completed, the gypsum-aerogel composite material was dried to obtain a surface hydrophobic gypsum-aerogel composite material.
[0039] Embodiment 2:
[0040] The difference between this embodiment and embodiment 1 is that the phosphogypsum, calcination temperature, calcination time, aging time, and water-powder ratio are selected.
[0041] (1) calcining phosphogypsum (from Hubei Xingfa Group, the same below) in an oven at 140° C. for 4 h and then aging it in an environment at 20° C. and a relative humidity of 80% for 1 day to obtain phosphogypsum powder;
[0042] (2) Phosphorus building gypsum powder and silica hydrophilic aerogel (purchased from Wuzhen Technology Group Hebei Co., Ltd., the same below), with a thermal conductivity of 0.018 W / (m·K), were dry-mixed and stirred evenly, and then water was added at a water-powder ratio of 1.2 mL / g to obtain a gypsum-aerogel mixed slurry;
[0043] (3) injecting the gypsum-aerogel mixed slurry into a mold, curing it for 3 days in an environment of 20° C. and a relative humidity of 80%, and then drying it to obtain a hydrophilic gypsum-aerogel composite material;
[0044] (4) Octadecyltrichlorosilane was dissolved in n-hexane to obtain an octadecyltrichlorosilane solution, and the hydrophilic gypsum-aerogel composite material was immersed in the octadecyltrichlorosilane solution at a mass volume ratio of 1.0 g / mL for 5 h, and the volume ratio of the solvent n-hexane to octadecyltrichlorosilane was 80 v / v. After the modification was completed, the gypsum-aerogel composite material was dried to obtain a surface hydrophobic gypsum-aerogel composite material.
[0045] Embodiment 3:
[0046] The difference between this embodiment and embodiment 1 is that different calcination temperatures, aging times, curing times, silane coupling agents, and impregnation times are selected.
[0047] (1) calcining the desulfurized gypsum in an oven at 180° C. for 3 h and then aging it at 20° C. and a relative humidity of 80% for 3 days to obtain desulfurized building gypsum powder;
[0048] (2) dry-mixing desulfurized building gypsum powder and silica hydrophilic aerogel (thermal conductivity of 0.018 W / (m·K)) and stirring evenly, then adding water at a water-powder ratio of 1.8 mL / g and stirring to obtain a gypsum-aerogel mixed slurry;
[0049] (3) injecting the gypsum-aerogel mixed slurry into a mold, curing it in an environment of 20° C. and a relative humidity of 80% for 1 day, and then drying it to obtain a hydrophilic gypsum-aerogel composite material;
[0050] (4) Dissolve trimethylchlorosilane in n-hexane to obtain a trimethylchlorosilane solution, and immerse the hydrophilic gypsum-aerogel composite material in the trimethylchlorosilane solution at a mass volume ratio of 1.0 g / mL for 5 hours, wherein the volume ratio of the solvent n-hexane to trimethylchlorosilane is 80 v / v. After the modification is completed, the gypsum-aerogel composite material is dried to obtain a surface hydrophobic gypsum-aerogel composite material.
[0051] Embodiment 4:
[0052] The difference between this embodiment and embodiment 1 is that different calcination times, water-powder ratios, hydrophobic modifier ratios, hydrophobic modifier addition mass-volume ratios, and impregnation times are selected.
[0053] (1) calcining the desulfurized gypsum in an oven at 160° C. for 1 h and then aging it at 20° C. and a relative humidity of 80% for 2 days to obtain desulfurized building gypsum powder;
[0054] (2) dry-mixing desulfurized building gypsum powder and silica hydrophilic aerogel (thermal conductivity of 0.018 W / (m·K)) and stirring evenly, then adding water at a water-powder ratio of 1.2 mL / g and stirring to obtain a gypsum-aerogel mixed slurry;
[0055] (3) injecting the gypsum-aerogel mixed slurry into a mold, curing it for 3 days in an environment of 20° C. and a relative humidity of 80%, and then drying it to obtain a hydrophilic gypsum-aerogel composite material;
[0056] (4) Octadecyltrichlorosilane was dissolved in n-hexane to obtain an octadecyltrichlorosilane solution, and the hydrophilic gypsum-aerogel composite material was immersed in the octadecyltrichlorosilane solution at a mass volume ratio of 1.5 g / mL for 5 h, and the volume ratio of the solvent n-hexane to octadecyltrichlorosilane was 100 v / v. After the modification was completed, the gypsum-aerogel composite material was dried to obtain a surface hydrophobic gypsum-aerogel composite material.
[0057] Comparative Example 1:
[0058] The difference between this comparative example and Example 1 is that no hydrophilic aerogel is added, and the specific steps are as follows:
[0059] (1) calcining the desulfurized gypsum in an oven at 160° C. for 3 h and then aging it in an environment at 20° C. and a relative humidity of 80% for 2 days to obtain desulfurized building gypsum powder;
[0060] (2) adding water to the desulfurized building gypsum powder at a water-powder ratio of 0.6 mL / g and stirring to obtain a gypsum slurry;
[0061] (3) after the gypsum slurry is injected into a mold, it is cured for 2 days in an environment of 20° C. and a relative humidity of 80%, and then dried to obtain a gypsum material with a hydrophilic surface;
[0062] (4) Octadecyltrichlorosilane was dissolved in n-hexane to obtain an octadecyltrichlorosilane solution, and the surface hydrophilic gypsum-aerogel composite material was immersed in the octadecyltrichlorosilane solution at a mass volume ratio of 1.0 g / mL for 5 h, and the volume ratio of solvent n-hexane to octadecyltrichlorosilane was 80 v / v. After the modification was completed, the gypsum-aerogel composite material was dried to obtain a surface hydrophobic gypsum-aerogel composite material.
[0063] Comparative Example 2:
[0064] The difference between this comparative example and Example 1 is that the hydrophobic impregnation modification step is not performed, and the specific steps are as follows:
[0065] (1) calcining the desulfurized gypsum at 160° C. in an oven for 3 h and then aging it at 20° C. and a relative humidity of 80% for 2 days to obtain desulfurized building gypsum powder;
[0066] (2) dry-mixing desulfurized building gypsum powder and silica hydrophilic aerogel (thermal conductivity of 0.018 W / (m·K)) and stirring evenly, then adding water at a water-powder ratio of 1.8 mL / g and stirring to obtain a gypsum-aerogel mixed slurry;
[0067] (3) The gypsum-aerogel mixed slurry was injection molded and then cured for 2 days in an environment of 20° C. and a relative humidity of 80% and then dried to obtain a gypsum-aerogel composite material with a hydrophilic surface.
[0068] Comparative Example 3:
[0069] The difference between this comparative example and Example 1 is that silica hydrophobic aerogel (purchased from Needle-Free Technology Group Hebei Co., Ltd.) is added, and the hydrophobic impregnation modification step is not performed. The specific steps are as follows:
[0070] (1) calcining the desulfurized gypsum in an oven at 160° C. for 3 h and then aging it in an environment at 20° C. and a relative humidity of 80% for 2 days to obtain desulfurized building gypsum powder;
[0071] (2) dry-mixing desulfurized building gypsum powder and hydrophobic aerogel (thermal conductivity of 0.015 W / (m·K)) and stirring evenly, then adding water at a water-powder ratio of 0.9 mL / g and stirring to obtain a gypsum-aerogel mixed slurry;
[0072] (3) The gypsum-aerogel mixed slurry was injection molded and then cured for 2 days in an environment of 20° C. and a relative humidity of 80% and then dried to obtain a gypsum-aerogel composite material.
[0073] The hydrophilic silica aerogels used in Examples 1 to 4 and the hydrophobic silica aerogels used in Comparative Example 3, the density, thermal conductivity and pore structure data of the two aerogels are shown in Table 1.
[0074] Table 1 Aerogel density, thermal conductivity and pore structure data
[0075]
[0076] Note: S BET -Specific surface area (m 2 / g); V T -Pore volume (cm 3 / g); D-average pore diameter (nm).
[0077] Comparative analysis of experimental results: The mechanical strength, density, thermal conductivity, softening coefficient and surface water contact angle data of the gypsum-aerogel composite materials prepared in Examples 1 to 4 and Comparative Examples 1 to 3 are shown in Table 2. By adding hydrophilic aerogel, the thermal conductivity of the gypsum material is reduced from 0.491W / (m·K) to 0.080W / (m·K), a decrease of more than 80%, and the thermal insulation performance is significantly improved. At the same time, the compressive and flexural strengths can still be maintained at more than 1.8 and 0.7MPa. Through hydrophobic impregnation modification, the hydrophobic properties of the gypsum-aerogel composite material are significantly improved, the softening coefficient is increased from 0.34 to more than 0.80, and the contact angle is increased from 0° to more than 120°, and there is no significant effect on the mechanical and thermal insulation properties of the gypsum-aerogel composite material. Compared with the composite material obtained by directly adding hydrophobic aerogel into gypsum in the existing process, the finished industrial by-product gypsum-aerogel composite insulation material obtained by this method has a smooth surface, no irregular pores, good aesthetics, excellent hydrophobic properties, and is sufficient to withstand humid environments. Figure 3 (a) is the morphology of the surface hydrophobically modified gypsum-aerogel composite thermal insulation material prepared in Example 1, Figure 3 (b) is the surface static water contact angle of the surface hydrophobically modified gypsum-aerogel composite thermal insulation material prepared in Example 1; Figure 4 (a) is the morphology of the industrial by-product gypsum-hydrophobic aerogel composite thermal insulation material prepared in Comparative Example 3. Figure 4 (b) is the static water contact angle on the surface of the industrial by-product gypsum-hydrophobic aerogel composite thermal insulation material prepared in Comparative Example 3; Figure 5 This is the XRD characterization diagram of the surface hydrophobic modified gypsum-aerogel composite thermal insulation material. It can be seen that hydrophilic CaSO4·2H2O exists in the surface hydrophobic modified gypsum-aerogel composite thermal insulation material.
[0078] Table 2 Mechanical strength, density, thermal conductivity, softening coefficient and surface water contact angle data of gypsum-aerogel composite materials prepared in different embodiments
[0079]
[0080]
[0081] It will be easily understood by those skilled in the art that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a surface hydrophobically modified gypsum-aerogel composite thermal insulation material, characterized in that: The following steps are involved: (1) mixing CaSO4·0.5H2O gypsum powder with a purity of 85%-95% and hydrophilic aerogel powder with a thermal conductivity of 0.01-0.02 W / (m·K) in a mass ratio of 3-6, then adding water, injection molding and curing, and then drying at 40-60° C. to obtain a hydrophilic gypsum-aerogel composite material; (2) The hydrophilic gypsum-aerogel composite material is immersed in a silane coupling agent solution for modification, and then dried to obtain a gypsum-aerogel composite material with a hydrophobic surface.
2. The method for preparing a surface hydrophobically modified gypsum-aerogel composite thermal insulation material according to claim 1, characterized in that: The CaSO4·0.5H2O gypsum powder is obtained by calcining and aging gypsum containing CaSO4·2H2O. The calcination temperature is 140-180°C, the calcination time is 1-4 hours, and the aging time is 1-3 days.
3. The method for preparing a surface hydrophobically modified gypsum-aerogel composite thermal insulation material according to claim 2, characterized in that: The CaSO4·2H2O-containing gypsum is one or more of desulfurized gypsum, phosphogypsum, fluorinated gypsum and citric acid gypsum.
4. The method for preparing a surface hydrophobically modified gypsum-aerogel composite thermal insulation material according to claim 3, characterized in that: The hydrophilic aerogel powder material is selected from one or more of silica aerogel, alumina aerogel and carbon aerogel, and the pore size of the hydrophilic aerogel powder is 20-40 nm.
5. The method for preparing a surface hydrophobically modified gypsum-aerogel composite thermal insulation material according to claim 4, characterized in that: In step (1), the ratio of the added volume of the water to the sum of the weights of the CaSO4·0.5H2O gypsum powder and the hydrophilic aerogel powder is 1.2 to 1.8 mL / g.
6. The method for preparing a surface hydrophobically modified gypsum-aerogel composite thermal insulation material according to claim 5, characterized in that: In step (1), the injection molding curing conditions are: curing temperature is 15-25° C., relative humidity is 80%-90%, and curing time is 1-3 days.
7. The method for preparing a surface hydrophobically modified gypsum-aerogel composite thermal insulation material according to claim 6, characterized in that: In step (2), the silane coupling agent solution is prepared by adding a silane coupling agent into a solvent, wherein the silane coupling agent is selected from one or more of trimethylchlorosilane, octadecyltrichlorosilane, and methyltrimethoxysilane, and the volume ratio of the solvent to the silane coupling agent is 80 to 100.
8. The method for preparing a surface hydrophobically modified gypsum-aerogel composite thermal insulation material according to claim 7, characterized in that: In step (2), the mass volume ratio of the hydrophilic gypsum-aerogel composite material to the silane coupling agent solution is 1.0 to 1.5 g / mL, and the immersion time is 3 to 5 hours.
9. A surface hydrophobic gypsum-aerogel composite material is prepared according to the method for preparing a surface hydrophobic modified gypsum-aerogel composite thermal insulation material according to any one of claims 1 to 8.
10. Use of the surface-hydrophobic gypsum-aerogel composite material according to claim 9, wherein the surface-hydrophobic gypsum-aerogel composite material is used as a thermal insulation material in a building.
Citation Information
Patent Citations
Organosilicon macromolecular composite waterproof gypsum and preparation method thereof
CN103113076A
Aerogel-containing gypsum material and preparation method thereof
CN106747189A
Aerogel composite and preparation method thereof
CN107266116A
Gypsum-based self-leveling mortar and preparation method thereof, and gypsum-based self-leveling slurry
CN109694228A
Preparation method of gypsum-based building exterior wall thermal insulation material
CN112174623A